The adopting factors of campus mobile software applications. (20th October 2020) - Wang, Wen-Cheng; Su, Chiu-Hung; Pai, Nai-Yuan
Many criteria are used for evaluating the quality of campus mobile software utilisation, though largest of those standards are interdependent or interactive, making it challenging to efficiently separate and enhance the position of campus mobile software applications. This study aims to solve this problem by using a various multicriteria decision-making approach, including decision-making trial and evaluation laboratory (DEMATEL), DEMATEL-based analytical network process (DANP), and the VIKOR method. The relationship between operating standards and value-added assistance content providers can be followed to determine relationship and feedback issues to fit the demands of the mobile communications trade.